Vemurafenib Limits Influenza A Virus Propagation by Targeting Multiple Signaling Pathways - Holzberg, Magdalena; Boergeling, Yvonne; Schräder, Tobias; Ludwig, Stephan; Ehrhardt, Christina (Frontiers in Microbiology, 2017)
Influenza A viruses (IAV) can cause severe global pandemic outbreaks. The currently licensed antiviral drugs are not very effective and prone to viral resistance. Thus, novel effective and broadly active drugs are urgently needed. We have identified the cellular Raf/MEK/ERK signaling cascade as crucial for IAV replication and suitable target for an antiviral intervention. Since this signaling cascade is aberrantly activated in many human cancers, several clinically approved inhibitors of Raf and MEK are now available. Here we explored the anti-IAV action of the licensed B-RafV600E inhibitor Vemurafenib. Treatment of B-RafWT cells with Vemurafenib induced a hyperactivation of the Raf/MEK/ERK cascade rather than inhibiting its activation upon IAV infection. Despite this hyperactivation, which has also been confirmed by others, Vemurafenib still strongly limited IAV-induced activation of other signaling cascades especially of p38 and JNK mitogen-activated protein kinase (MAPK) pathways. Most interestingly, Vemurafenib inhibited virus-induced apoptosis via impaired expression of apoptosis inducing cytokines and led to hampered viral protein translation most likely due to the decreased activation of p38 and JNK MAPK. These multiple actions resulted in a profound and broadly active inhibition of viral replication, up to a titer reduction of three orders of a magnitude. Thus, while Vemurafenib did not act similar to MEK inhibitors, it displays strong antiviral properties via a distinct and multi-target mode of action.